The Important Role of Pancasila and Its Challenges at SMKN 2 Gerung in the Digital Era - Dini Iza Septiana; Harkatun Hasanah; Fidiatun; Elda Wati; Hera Sukma Rahmaniah; Zubair (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study discusses the important role of Pancasila and its challenges at SMKN 2 Gerung in the digital era. The purpose of this study is to find out teachers in implementing Pancasila values in the digital era. This study uses a qualitative method with a descriptive approach, namely data collection through interviews, observations and documentation. It explores how the role and challenges of teachers in implementing Pancasila values in this digital era. The interview was conducted with one of the teachers, namely Mrs. Tanti Rizkian Sari, S.Pd. on December 5, 2024. The results show that many children are influenced by foreign cultures such as negative content that causes students to be less able to apply Pancasila values. This study is expected to provide useful insights for teachers to apply Pancasila values.